IMPLEMENTING PRECISION TECHNOLOGY IN AGRICULTURE TO OPTIMIZE PRODUCTIVITY AND AGRICULTURAL SUSTAINABILITY (CIPEEX, 2025)
Precision agriculture represents a breakthrough in the field, providing an innovative and efficient approach to agricultural activities. Based on the use of advanced technologies such as Geographic Information Systems (GIS), remote sensing, drones and automated machinery, this methodology allows for more detailed and specific management of cultivated areas. The result is increased productivity and sustainability, optimizing the use of inputs such as water, fertilizers and pesticides, minimizing waste and reducing environmental impact. Sensors and monitoring systems provide precise information on soil conditions, plant health and the presence of pests and diseases. The aim of this study is to analyze the benefits of precision agriculture based on studies from the LILACS, SCIELO and CAPES databases. The methodology used was a bibliographic review, applying inclusion criteria that cover articles available in these databases between the years 2019 to 2024. Search terms such as "precision agriculture", "drones", "automated agricultural management", among others relevant to the topic, were used. Duplicate documents, opinion articles and case reports were excluded from the initial analysis, resulting in a final set of 7 studies for analysis. One of the main benefits of precision agriculture is its ability to increase production efficiency. With the precise application of inputs, costs can be reduced and production maximized. These technologies automatically adjust the amount of water according to the specific needs of each area of the field. In addition, fertilization and pesticide application can be done in a more controlled manner, avoiding overdosing and contamination of soil and water. Another crucial aspect is sustainable practices which promote the rational use of natural resources and the preservation of the environment. Reducing the use of chemical inputs reduces greenhouse gas emissions, helping to reduce climate change. This technology facilitates the traceability of agricultural operations, providing greater transparency and control over the production chain. This is important to meet consumer demands for high quality, sustainably sourced products. However, the implementation of precision technology in agriculture faces significant challenges. These include the high initial cost of the equipment and the need for technical training for farmers. The integration of these technologies requires investments in infrastructure, training and ongoing support for maintaining and updating the systems. In short, precision technology represents an indispensable advance in the modernization of the agricultural sector, promoting productivity optimization and sustainability. By providing tools for more efficient and sustainable management, precision agriculture has the potential to transform production, benefiting both farmers and the environment. To maximize the benefits, it is essential to promote policies to encourage and support the adoption of these technologies, ensuring that farmers can access and use these innovations effectively
Keywords: precision agriculture; sustainability; technology; productivity